747 YouTube And Neurosurgery: Better Content, More Views. (4th May 2021) - Mayo, I; Manivannan, S; Bisson, J; Leach, P; Zaben, M
Abstract: Introduction: YouTube is the world's largest open-access media sharing platform and contains much content on Neurosurgery. Inserting an External Ventricular Drain is a common procedure, often performed by neurosurgical trainees to treat emergency hydrocephalus. We set out to evaluate the content on EVD insertion posted on YouTube and its usefulness for trainees in learning the procedure Method: A YouTube keyword search was conducted to identify videos on EVD insertion. Inclusion criteria was used to find videos specifically aimed to EVD insertion. We devised a scoring sheet to give each video an educational score (0-20), which two independent reviewers used to analyse the included videos. Results: A total of 12/556 videos met the inclusion criteria. Dates posted ranged from 01/07/2012 to 24/04/2019, with views ranging from 359 – 166, 388 (mean 30531, SD 49, 570). The mean educational score was 6.91 (SD 3.86), with only four videos scoring 10 or greater. There was a strong correlation between viewership and educational score (R .085 p <.001). Conclusions: The majority of YouTube content relating to EVD insertion is not useful to trainees, but useful content can attract a greater viewership. There is an opportunity for Neurosurgeons and Institutions to gain exposure on YouTube with high-quality open-access educational content.